Rasionalitas Pemberian Antibiotik Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita di Puskesmas Jamanis - Fauziah, Elsa; Eddy Suhardiana; Srie Rezeki Nur Endah (Pusat Riset dan Inovasi Nasional, 2023)
Respiratory tract infections are one of the causes of high mortality and morbidity in children, especially in children under the age of 5 years whose immune system is still susceptible to various diseases. The purpose of this study was to determine the rationality of giving antibiotics for acute respiratory tract infections (ARI) to toddlers at the Jamanis Health Center. The type of research used is descriptive research, the sampling method is purposive sampling and data collection is carried out retrospectively. Then data analysis was carried out and compared with references from MTBS guidelines. This research was conducted at the Jamanis Health Center when the research was conducted in March-May 2023. The population used in this study was all ARI patients at the Jamanis Health Center for the January-December 2022 period. Based on the data obtained, the number of medical records of ARI patients in toddlers at the Jamanis Health Center for the 2022 period is 1121 people. The results of the study of the most widely used antibiotic drug were amoxicillin with 82 cases (89.13%). The results of rationality of drug administration based on the criteria of Right diagnosis that is equal to 100% (Rational), Right indication that is equal to 65.21% (Not Rational), Right drug that is equal to 65.21% (Not Rational), Right patient that is equal to 100% (Rational), Right dose that is equal to 100% (Rational)